Accounting for qualification in mismatch unemployment - Anja Bauer (Journal for Labour Market Research, 2024)
The paper shows how important it is to consider the requirement level when measuring mismatch unemployment. While the mismatch between occupations decreases over time, the imbalances in the distribution of unemployed workers and vacant jobs across requirement levels increased, which, in sum, led to a stagnation of mismatch on the combined occupation-requirement level. Furthermore the paper shows that mismatch unemployment emerges especially at the level of un- and semi-skilled activities, as there is excess supply regardless of the occupations. And, more importantly, the excess supply is rising recently.
Keywords: E24; J6; 330; Allocation; Job finding rate; Mismatch; Occupation; Qualification